ChemInform Abstract: Conformationally Restricted Pyrrolidines by Intramolecular [2 + 2] Photocycloaddition Reactions. Issue 29 (1st July 2013) - Fort, Diego A.; Woltering, Thomas J.; Nettekoven, Matthias; Knust, Henner; Bach, Thorsten
Abstract The reaction proceeds with high regioselectivity.